2014
DOI: 10.1007/s13319-014-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Image Compression Algorithm for High Resolution 3D Reconstruction

Abstract: This research presents a novel algorithm to compress high-resolution images for accurate structured light 3D reconstruction. Structured light images contain a pattern of light and shadows projected on the surface of the object, which are captured by the sensor at very high resolutions. Our algorithm is concerned with compressing such images to a high degree with minimum loss without adversely affecting 3D reconstruction. The Compression Algorithm starts with a single level discrete wavelet transform (DWT) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…An analysis of 2D image compression and 3D data compression algorithms developed within the GMPR group is presented here from a compression-encryption perspective. We show that the proposed methods provide simultaneous efficient compression-encryption of data for both 2D images and 3D data structures (Siddeq and Rodrigues, 2016;2015a;2015b;2014a;2014b). In Siddeq and Rodrigues (2014b) we proposed a novel 2D image compression method based on high-frequency sub-bands.…”
Section: The Gmpr Compression-encryption Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of 2D image compression and 3D data compression algorithms developed within the GMPR group is presented here from a compression-encryption perspective. We show that the proposed methods provide simultaneous efficient compression-encryption of data for both 2D images and 3D data structures (Siddeq and Rodrigues, 2016;2015a;2015b;2014a;2014b). In Siddeq and Rodrigues (2014b) we proposed a novel 2D image compression method based on high-frequency sub-bands.…”
Section: The Gmpr Compression-encryption Methodsmentioning
confidence: 99%
“…We present an algorithmic solution that has been demonstrated for compression of image and 3D data structures (Siddeq and Rodrigues, 2016;2015a;2015b;2014a;2014b). A unique, data-dependent symmetric key is generated as a side effect to the compression method.…”
Section: Introductionmentioning
confidence: 99%
“…(8) can later be recovered by estimating the key values for that block [13,20,21]. However, this problem is underdetermined and extra information is required.…”
Section: High-frequency Minimization Algorithmmentioning
confidence: 99%
“…For this reason, high-frequencies values in this region are quantized. The quantization process in this research depends on the maximum value in each sub-band, as shown by the following equation (Siddeq, 2014b):…”
Section: Two Level Discrete Wavelet Transform (Dwt)mentioning
confidence: 99%